Secular Traits of Śruti: Exploring its Methodological Implications in the Eastern Epistemic Tradition - Phuyal, Komal Prasad (Nepal Journal of Multidisciplinary Research, 2026)
Background: In the Eastern tradition of knowledge formation and transmission, śruti emerges as the pivotal canon, in which people participate as both experiencers and recipients of knowledge. However, knowledge is never treated as an individual achievement in the East. The knowledge that people directly experience, as revealed to them through deep contemplation, reflection, and observation of the natural world, forms a solid foundation for its transmission to later generations through oral tradition. The paper aims to approach śruti as a body of knowledge in the Vedas and then examine it as a method of knowledge within the epistemic tradition of the East. Methods: This paper provides a historical analysis of the scholarship on śruti as a social practice in knowledge formation and transfer in the East. By examining historical and textual data, the paper relocates śruti in the contemporary critical debate and examines it as a means of knowledge. The Eastern body of literature on such knowledge refers to this phenomenon as the divine as opposed to human implied in smriti. Results: The present study explores that śruti emanates from the secular roots even though the contemporary practice treats it as the devotional, sectarian practice founded in the Vedas. The foundation of knowledge building is laid with śruti as the approach of reasoning in the Vedic texts. Conclusion: This paper situates the tradition within the contemporary debate on knowledge and epistemology, reading the historical development of śruti in the larger historical backdrop and examining the pedagogical implications in modern academic practice. Novelty: This study significantly contributes to the ongoing critical dialogue on indigenous pedagogy in the larger backdrop of postcolonial curricular reforms and śruti as the mode of reasoning and knowledge building in the East.